Cuerpo, practicas sociales y modernidad. Tecnologías y representaciones de la corporalidad en la transformación europea, siglos XVI al XVIII (2004)
The construction of Modernity in Europe is not a social transformation process that has been developed only or mainly on the level of ideas. It is more like small, multiform processes that have converged in different local, national, and continental contexts, and have involved the corporal practices of every day life. This article reads that transformation, not from an ideological perspective, but from a ìtechnologicalî one, in terms of Foucault. Technologies that affect from epistemological frameworks to daily sensibilities. The great hegemonic task has been to subject the ìmultitudesî to new technologies of control, the popular masses growing in political visibility.